2016
DOI: 10.1016/j.midw.2016.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Community-based birth waiting homes in Northern Sierra Leone: Factors influencing women's use

Abstract: some barriers, especially those related to family commitments and costs of food, are challenging to solve. In order to make a BWH a user-friendly and viable option, it may be necessary to adjust ways in which BWHs are used. Good linkage with the health system is strength of the programme. However, further strengthening of community participation in monitoring and managing the BWHs is needed for the long term success and sustainability of the BWHs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 19 publications
3
39
1
Order By: Relevance
“…10 In contrast, no direct costs of using MWH to the woman were reported in previous studies from Timor-Leste, Ethiopia, and Sierra Leone. 11,17,21 The substantial nonmedical costs compared with medical costs among MWH users in our study were similar to the findings of a previous study from Ethiopia, which revealed that cost of transportation was the main reason for the delay of pregnant women in reaching the health facility and not using MWH. 21 A Nicaraguan study reported that more than 60% of OOP payments for delivery care were indirect expenses for MWH users, with no comparable indirect expenses for home deliveries.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…10 In contrast, no direct costs of using MWH to the woman were reported in previous studies from Timor-Leste, Ethiopia, and Sierra Leone. 11,17,21 The substantial nonmedical costs compared with medical costs among MWH users in our study were similar to the findings of a previous study from Ethiopia, which revealed that cost of transportation was the main reason for the delay of pregnant women in reaching the health facility and not using MWH. 21 A Nicaraguan study reported that more than 60% of OOP payments for delivery care were indirect expenses for MWH users, with no comparable indirect expenses for home deliveries.…”
Section: Discussionsupporting
confidence: 89%
“…For example, in our study, the medical expense of ultrasound examinations during an MWH stay was reported, whereas in Guatemala, the admitted women reported that they had to pay for the costs of their stay and meals . In contrast, no direct costs of using MWH to the woman were reported in previous studies from Timor‐Leste, Ethiopia, and Sierra Leone …”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…Past experience of childbirth, distance and cost of transportation to health facility were equally associated with ANC use [13]. Previous studies found that Income and education for women affect WTP for maternal health [6,14].…”
Section: Discussionmentioning
confidence: 99%